A conceptual model of nurses' workplace social capital: a theory synthesis - Jiamin Xu; Azadeh T. Stark (BMC, 2021)
Abstract Background Research has confirmed the importance of workplace social capital in the nursing workforce. Integration of the empirical evidence about nurses' workplace social capital into a scientific collection can provide a comprehensive presentation of this concept. This scientific collection can be a conduit for further research and advancement of nursing management and leadership. The purpose of this paper, therefore, is to discuss the process of developing a conceptual model of nurses' workplace social capital, an effective and concise approach to illustrate a scientific phenomenon. Methods The model of nurses' workplace social capital was developed following Walker and Avant's strategy of theory synthesis. Empirical evidence relevant to nurses' workplace social capital was synthesized by systematically examining the existing literature. PubMed, CINAHL, Web of Science and Google Scholar were searched periodically from October 2017 to July 2020. Results Our proposed conceptual model lays out the determinants and outcomes of nurses' workplace social capital and specifies the relational statements among these concepts. Nurses' workplace social capital is influenced by the organizational and individual determinants shaped by multiple layers of sub-concepts. The development and implementation of nurses' workplace social capital has three themes of consequences: 1) nurses' outcomes; 2) patients' outcomes; and 3) organizational outcomes. All the concepts and statements have been organized and aligned with the principles of "inventory of determinants or results" and "theoretical blocks". Conclusion Our theoretical synthesis offers a comprehensive picture of the current knowledge of nurses' workplace social capital. Efforts should be dedicated to evaluating, revising, and revamping this newly developed model based on future empirical evidence. Our synthesized conceptual model is the segue to more comprehensive studies about nurses' workplace social capital. Interventional programs for the development of social capital can be structured based on the identified determinants.